2017
DOI: 10.1371/journal.pone.0169496
|View full text |Cite
|
Sign up to set email alerts
|

Splenic CD4+ T Cells in Progressive Visceral Leishmaniasis Show a Mixed Effector-Regulatory Phenotype and Impair Macrophage Effector Function through Inhibitory Receptor Expression

Abstract: Visceral leishmaniasis (VL), caused by infection with the intracellular protozoan Leishmania donovani, is a chronic progressive disease with a relentlessly increasing parasite burden in the spleen, liver and bone marrow. The disease is characterized by fever, splenomegaly, cachexia, and pancytopenia, and progresses to death if not treated. Control of Leishmania infection is mediated by Th1 (IFNγ-producing) CD4+ T cells, which activate macrophages to produce nitric oxide and kill intracellular parasites. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 61 publications
3
40
0
Order By: Relevance
“…It has also been observed that during sub-clinical L. donovani infection, enhanced percentages of CD4 þ T cells resulted in disease control. 38 In the present study, a significant decline in the CD4 þ T cell population was observed in the infected animals compared with the normal controls, whilst the treatment of animals with Iodium 30c led to significant reversal of the suppressed immune response. This is evident also in patients with active VL, where a higher population of CD8 þ T cells than CD4 þ T cells has been observed, which reverted to normal levels following subsequent treatment.…”
Section: T Cells and Subsetssupporting
confidence: 48%
“…It has also been observed that during sub-clinical L. donovani infection, enhanced percentages of CD4 þ T cells resulted in disease control. 38 In the present study, a significant decline in the CD4 þ T cell population was observed in the infected animals compared with the normal controls, whilst the treatment of animals with Iodium 30c led to significant reversal of the suppressed immune response. This is evident also in patients with active VL, where a higher population of CD8 þ T cells than CD4 þ T cells has been observed, which reverted to normal levels following subsequent treatment.…”
Section: T Cells and Subsetssupporting
confidence: 48%
“…This approach of using differential transcriptome analysis as a tool to understand Leishmania-host interactions has been successfully employed in several animal models and in vitro studies. Despite differences related to experimental models (Syrian hamster/mice/ in vitro macrophages) and methodology (RNA-seq/qPCR/microarray hybridization) all of them draw a picture of mixed responses during infection and deactivation of effective parasite-controlling responses (Rabhi et al, 2012 ; Dillon et al, 2015 ; Fernandes et al, 2016 ; Kong et al, 2017 ; Medina-Colorado et al, 2017 ). Similar to our study, transcriptional profile of spleen samples from L. donovani -infected hamsters was analyzed 28 days after infection, revealing a strikingly proinflammatory environment and a strong expression of Ifng that did not protect against the increasing parasite burden (Kong et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our study, transcriptional profile of spleen samples from L. donovani -infected hamsters was analyzed 28 days after infection, revealing a strikingly proinflammatory environment and a strong expression of Ifng that did not protect against the increasing parasite burden (Kong et al, 2017 ). Likewise, chronic infection in hamsters revealed expression of markers of both T cell activation and inhibition, showing mixed expression of Th1 and Th2 cytokines and chemokines, and again ineffective in controlling infection (Medina-Colorado et al, 2017 ). Those studies that focused on the evaluation of early stages of infection (Dillon et al, 2015 ; Fernandes et al, 2016 ) revealed upregulation of both pro- and anti-inflammatory related genes similarly to our findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has examined whole blood transcriptional responses in healthy controls versus asymptomatic and symptomatic VL patients in Brazil 39 . Three studies have evaluated transcriptional changes in the spleen of hamsters infected with L. donovani 40 42 . Here, we have applied transcriptional profiling to address key aspects of the tissue specific response to L. donovani infection in mice.…”
Section: Introductionmentioning
confidence: 99%